SOCIAL MEDIA USER PERSONALITY CLASSIFICATION BASED ON HOW USER LIVE AND MAKE DECISION - Chamadani Faisal Amri; Sri Suryani Prasetyowati; Yuliant Sibaroni (STKIP PGRI Tulungagung, 2022)
Personality classification is one of the ways in the field of Natural Language Processing (NLP) with a collection of data that can describe the user's personality through input sets of text documents such as status uploads. Social media is one way to interact online that can provide convenience for users, such as interacting, expressing themselves, and expanding friendships. Status posts on social media can be extracted into useful information in the personality classification process. This research performs classification based on how social media users live their lives and make decisions, which is a representation of the